Enhanced photocurrent generation of bio-inspired graphene/ZnO composite films1. Issue 22 (14th June 2015) - Yin, Shengyan; Men, Xiaoju; Sun, Hang; She, Ping; Zhang, Wei; Wu, Changfeng; Qin, Weiping; Chen, Xiaodong
<x xml:space="preserve">Abstract</x> A bio-inspired honeycomb graphene/ZnO composite photoelectrode is developed, which shows a decreased light reflection and an increased photocurrent.